2015
DOI: 10.1177/1535370215609693
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated calcium entry and diabetic complications

Abstract: Store-operated Ca 2þ entry (SOCE) is mediated by the store-operated Ca 2þ channel (SOC) that opens upon depletion of internal Ca 2þ stores following activation of G protein-coupled receptors or receptor tyrosine kinases. Over the past two decades, the physiological and pathological relevance of SOCE has been extensively studied. Recently, accumulating evidence suggests associations of altered SOCE with diabetic complications. This review focuses on the implication of SOCE as it pertains to various complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 165 publications
0
19
0
Order By: Relevance
“…STIM1 protein functions as an ER Ca 2+ sensor, which clusters proximally to plasma membranes to activate Orai1 during ER Ca 2+ depletion 26 , 27 . Accumulating evidence indicates that altered SOCE is associated with diabetes complication 28 , 29 . Studies show that depletion of intracellular Ca 2+ stores in β cells activate SOCE 25 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…STIM1 protein functions as an ER Ca 2+ sensor, which clusters proximally to plasma membranes to activate Orai1 during ER Ca 2+ depletion 26 , 27 . Accumulating evidence indicates that altered SOCE is associated with diabetes complication 28 , 29 . Studies show that depletion of intracellular Ca 2+ stores in β cells activate SOCE 25 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of SOCE for artery function in diabetes has been controversially discussed, 27 partly on account of inconsistent data obtained from different species, various models of diabetes, and diverse vascular beds. For example, a reduced SOCE‐dependent contraction has been measured in smooth muscle strips isolated from caudal arteries of type 2 diabetic Goto‐Kakizaki rats 28 .…”
Section: Discussionmentioning
confidence: 99%
“…SOCE was first identified as a major component of non-excitable cells, but further research has identified SOCE within a multitude of tissue types (Parekh and Putney, 2005). This knowledge has revealed it to be a ubiquitous Ca 2+ signaling pathway that regulates numerous cellular functions including those connected with diabetic complications (Chaudhari and Ma, 2016). Identification of SOCE mechanisms within adipocytes may lead to a better understanding of the onset of obesity and metabolic disorders and reveal therapeutic possibilities.…”
Section: Discussionmentioning
confidence: 99%